Vaccination services in community pharmacy practice: a scoping review - Ryan, Theo (My University, 2024)
Introduction: Vaccination services in community pharmacy practice is an important advancement in public health and has increased since the COVID-19 pandemic. The extent of vaccination in community pharmacy practice and stakeholders’ views of vaccination services has not been recently reported. Aim: This scoping review explores the provision of vaccinations in community pharmacy (vaccine type and to which patient groups provided) and key stakeholders’ (patients/carers and pharmacists) views of the vaccination services provided. Methods: The study was registered with Open Science Framework, and Joanna Briggs Institute guidance was used to define the following inclusion criteria:[1-2] Participants: Studies involving patients of any age and other demographic variables receiving a vaccination service in any community pharmacy setting. Concept: Studies that reported on the implementation and evaluation of all vaccination services provided by pharmacists in the community pharmacy setting. Evaluation studies of vaccination services considered evaluation by patients and pharmacists. Context: Studies involving provision of vaccination services by pharmacists in community pharmacy in any geographical location. Vaccination services provided by other healthcare professionals were not included. Searches were performed in CINAHL, EMBASE and MEDLINE (EBSCO) on 06/03/2023 using database-relevant controlled vocabulary (e.g., ‘pharmacy’, ‘vaccination’ and ‘service’). Grey literature searching was undertaken in MedNar. All study designs were considered for inclusion without publication date limits. Titles and abstracts were reviewed independently by two researchers and discrepancies resolved via discussion. Data extraction was undertaken using a modified JBI data extraction form. A mixed methods approach to data synthesis was used, with study characteristics analysed quantitatively and patients’/pharmacists’ views on vaccination services analysed qualitatively. Results: A total of 3245 records were identified from the database searches for screening, with a further 211 from the grey literature. A total of 102 studies were included. Most studies were undertaken in the United States of America (43; 42.2%), Canada (17; 16.7%) and the UK (8; 7.8%). Study types included cross-sectional (67; 65.7%), retrospective observational studies (15; 14.7%) and non-systematic reviews (10; 9.8%). The influenza vaccine (40; 39.2%) was most commonly provided, followed by COVID-19 (14; 13.7%). Other vaccines provided included herpes zoster and human papillomavirus. Vaccinations were targeted to all age-groups relevant to the vaccine supplied. Patient satisfaction rates were high across various countries with experiences focussing on access, professionalism and quality of information provided. Pharmacists reported having a positive outlook on their role in providing vaccination services. Pharmacists viewed vaccination services based in community pharmacies as an opportunity to contribute to the well-being of their communities and improve immunisation rates. Pharmacists also reported barriers to vaccine service provision which included regulation, training, remuneration and storage, which may consequently limit service expansion. Conclusion: A range of vaccines are available in community pharmacy, which has led to increases in patients availing of vaccination services. Patients’ and pharmacists’ perceptions towards the service are positive. Future research could address barriers, identified by pharmacists, which prevent expansion of vaccination services. Screening and data extraction involving seven reviewers was a strength of the study. As a scoping review, the study is limited as records were not quality appraised.
PUBLISHED
Keywords: Family medicine; MEDICINE; NURSING; PHARMACY PRACTICE; Pharmacy; VACCINATION; Virology; community pharmacy